Análise genética da concentração de potássio eritrocitário em bovinos - Caminhas, MMT; Bortolozi, J.; Chamma, O. J.; Kohayagawa, A. (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 1992)
Red-cell potassium concentration was determined in five breeds of cattle: Brown Swiss, Nelore, Pitangueiras, Gir and Girolanda. All the cattle examined for the red cell potassium concentration presented low potassium concentration or LK type. This were divided in the following sub-types: low-low potassium concentration (LLK variation: 7.0 -15.9 m-equiv/l) in 16.9% of the animals; medium-low potassium concentration (MLK variation: 16.0 - 30.9 m-equiv/l) in 77% of animals and high-low potassium concentration (HLK variation: 31.0 - 50.0 m-equiv/l) in 6.1% of the animals. This results may be associated with a tropical environment because animals whith red-cell potassium concentration have advantage in this environment.

No presente trabalho foi analisada a concentração de K eritrocitário em 148 bovinos das raças: Pardo-Suíço, Nelore, Pitangueiras, Gir e Girolanda. Todos os animais apresentaram baixa concentração de K eritrocitário ou tipo LK. Houve a presença dos três subtipos de LK conhecidos: LLK ou concentração baixa-baixa em 16,9% dos animais, variando de 7,0 a 15,9 meq/l, MLK ou concentração baixa-média em 77% dos animais, variando de 16,0 a 30,9 meq/l e HLK ou concentração baixa-alta em 6,1% dos animais, variando de 31,0 a 50,0 meq/l. Estes resultados podem ter significado biológico, já que as raças de gado melhor adaptadas às regiões tropicais apresentam baixa concentração de K eritrocitário.
Genetic-analysis of erythrocyte potassium concentration in cattle
Keywords: RED-CELL POTASSIUM CONCENTRATION; BROWN SWISS; NELORE; PITANGUEIRAS; GIR; GIROLANDA